Identification of Giardia lamblia, Entamoeba histolytica and Cryptosporidium sp. in Feces of Diarrheal Patient at Puskesmas Jatinangor, September–November 2012 - Komathi Palani; Lia Faridah; H. Uun Sumardi (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Diarrhea is one of the main public health problems occurring in West Java. One of the affected areas is Subdistrict Jatinangor. Inappropriate management of sanitation facilities around Jatinangor area causes contamination of water. Cikeruh River is one of the water sources in Jatinangor Area, from which people obtain water for daily activities. Water borne illness due to poor sanitation condition can lead to parasitic infection such as Giardia lamblia, Entamoeba histolytica and Cryptosporidium parvum whichcan cause a prolonged diarrhea. There has not been any study done regarding the presence of parasitical infection causing diarrhea around Jatinangor.Methods: In order to identify the parasitic infection, a descriptive study was carried out on 16 fecal samples collected from diarrheal patient who visited Puskesmas Jatinangor from September–November 2012. The parasites were checked by using wet mount methodResults: The parasites found were Entamoeba histolytica, Cryptosporidium parvum, but none of Giardia lamblia. There were also other findings such as Iodamoeba butschlii and Entamoeba coli.Conclusion: Positive findings of Entamoeba histolytica and Cryptosporidium parvum in diarrhea patients is most probably due to contaminated water and food. Measures need to be done to improve sanitary condition in Cikeruh River to prevent diarrhea. [AMJ.2015;2(1):213–16]